Classical Dermatomyositis: A Case Report - Pokhrel S; Pardhe BD; Giri N; Pokhrel R; Paudel D (Dove Medical Press, 2020)
Sushant Pokhrel,1,2 Bashu Dev Pardhe,1,3 Nisha Giri,2 Rakesh Pokhrel,2,4 Deliya Paudel2,5 1Department of Laboratory Medicine, Manmohan Memorial Institute of Health Sciences, Kathmandu, Nepal; 2Modern Diagnostic Laboratory and Research Center, Kathmandu, Nepal; 3Department of Life Science and Biochemical Engineering, Sun Moon University, Asan-Si, Chungnam, South Korea; 4Institute of Medicine, Tribhuvan University, Kathmandu, Nepal; 5Manmohan Memorial Medical College and Teaching Hospital, Kathmandu, NepalCorrespondence: Sushant PokhrelDepartment of Laboratory Medicine, Manmohan Memorial Institute of Health Sciences, PO Box No: 15201, Kathmandu, NepalTel +977-1-4030781Email Sushant.pokhrel@mmihs.edu.npAbstract: Dermatomyositis is an idiopathic myopathy involving progressive muscle weakness with skin manifestation. Diagnosis is based upon the progressive muscle weakness, skin rashes, elevated serum muscle enzymes, muscle biopsy, and abnormal electromyogram. The incidence of dermatomyositis is rare. In this case study, we report a case of classical dermatomyositis without incidence of malignancy. Timely diagnosis and administration of steroid led to better prognosis of the patient.Keywords: dermatomyositis, myopathy, creatinine phosphokinase